Managing Substance Use Disorders and Addiction: How to Integrate Professionalism and Ethics with the Complexity of Diagnosis and Therapy - Nurunnabi, Abu Sadat Mohammad; Nahar, Saifun; Akhter, Nasrin; Shaikh, Muhammad Abdul Kayum; Rahman, Md Ferdous; Sultan, Mohammad Tipu (Mugda Medical College Journal, 2024)
Physicians and other healthcare staff who work with the patients having substance use disorders (SUDs) and addiction have to deal with different and complex scenario invariably in comparison to other healthcare providers dealing with regular medical services sought by the patients. Hence, the unconventional nature of practice regarding patients of SUDs and addiction and the diverse range of backgrounds among substance use workers, e.g., psychiatrist, general physician, nurse, psychotherapist, counsellor, social worker, and public health specialist highlights the universal relevance of being more professional and more ethical in practice. They are expected to demonstrate a variety of ethical and professional competences to safeguard themselves and others involved. Clinical team engaged in such activities requires specific ethical training that can help them face specific ethical dilemmas and guide through deeper consideration of those pressing and complex issues, using specific framework, professional guidelines, or institutional management approaches. Professional societies and accrediting institutions should apply their authority to establish practice standards, competencies, regulatory procedures, and codes of ethics to help guide practice and protect public trust and confidence. For the team involved in practice, it is important to become familiar with and adhere to the principles and values that define professionalism and ethical conduct in care for patients suffering from SUDs and addiction. The review paper aims to examine the intersection of professionalism and ethics with the complexity of diagnosis and therapy in this specific area of practice. Besides, some frameworks will be highlighted which may help healthcare providers to foster ethical decision making. It is also a modest effort to show some new insights for improving the quality of care in addiction and mental health by the professional team and healthcare organization from both clinical and operational viewpoint. Mugda Med Coll J. 2024; 7(1): 42-47